Superoxide generation and leukocyte accumulation: key elements in the mediation of leukotriene B4‐induced itch by transient receptor potential ankyrin 1 and transient receptor potential vanilloid 1. Issue 4 (27th December 2012) - Fernandes, Elizabeth S.; Vong, Chi Teng; Quek, Samuel; Cheong, Jessica; Awal, Salma; Gentry, Clive; Aubdool, Aisah A.; Liang, Lihuan; Bodkin, Jennifer V.; Bevan, Stuart; Heads, Richard; Brain, Susan D.
Abstract : The underlying mechanisms of itch are poorly understood. We have investigated a model involving the chemoattractant leukotriene B4 (LTB4 ) that is up‐regulated in common skin diseases. Intradermal injection of LTB4 (0.1 nmol/site) into female CD1 mice induced significant scratching movements (used as an itch index) compared with vehicle‐injected (0.1% bovine serum albumin‐saline) mice. Intraperitoneal transient receptor potential (TRP) channel antagonist treatment significantly inhibited itch as follows: TRP vanilloid 1 (TRPV1) antagonist SB366791 (0.5 mg/kg, by 97%) and the TRP ankyrin 1 (TRPA1) antagonists TCS 5861528 (10 mg/kg; 82%) and HC‐030031 (100 mg/kg; 76%). Leukotriene B4 receptor 2 antagonism by LY255283 (5 mg/kg i.p.; 62%) reduced itch. Neither TRPV1‐knockout (TRPV1‐KO) nor TRPA1‐knockout (TRPA1‐KO mice exhibited LTB4 ‐induced itch compared with their wild‐type counterparts. The reactive oxygen species scavengers N ‐acetylcysteine (NAC; 204 mg/kg i.p.; 86%) or superoxide dismutase (SOD; 10 mg/kg i.p.; 83%) also inhibited itch. LTB4 ‐induced superoxide release was attenuated by TCS 5861528 (56%) and HC‐030031 (66%), NAC (58%), SOD (50%), and LY255283 (59%) but not by the leukotriene B4 receptor 1 antagonist U‐75302 (9 nmol/site) or SB366791. Itch, superoxide, and myeloperoxidase generation were inhibited by the leukocyte migration inhibitor fucoidan (10 mg/kg i.v.) by 80, 61, and 34%, respectively. Myeloperoxidase activity was also reduced by SB366791 (35%) and SOD (28%). TRPV1‐KO mice showed impaired myeloperoxidase release, whereas TRPA1‐KO mice exhibited diminished production of superoxide. This result provides novel evidence that TRPA1 and TRPV1 contribute to itch via distinct mechanisms.—Fernandes, E. S., Vong, C. T., Quek, S., Cheong, J., Awal, S., Gentry, C., Aubdool, A. A., Liang, L., Bodkin, J.V., Bevan, S., Heads, R., Brain, S.D. Superoxide generation and leukocyte accumulation: key elements in the mediation of leukotriene B4 ‐induced itch by transient receptor potential ankyrin 1 and transient receptor potential vanilloid 1. FASEB J. 27, 1664–1673 (2013). www.fasebj.org